ANALISIS BRAND IMAGE DAN BRAND AWARNESS PUPUK BIO ORGANIK (Studi pada Petani Pengguna Pupuk Merek “POMI” di Kota Batu) - Agustina Shinta; Abdul Wahib Muhaimin; Fikriah Fikriah; Palupi Palupi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This study examines  brand image and  brand awareness based on selected attributes of bio-organic fertilizer product brand "Pomi". The purpose of this study is to analyze  brand image,   the attributes of bio-organic fertilizer product brand  "Pomi" and analyze the brand awareness  .  Attributes are considered peasants were analyzed by  using  Cochran  Q,  then  is  used  to  measure  brand  awareness.  Determination  of levels of awareness of the brand  and brand image  owned by the respondent is based on the total score from the Likert scale values obtained in  the overall indicator.The result    of brand image is based on three variables: Variable  of  strength, the average value  (mean)  overall  strength  variable  is  4.26.  Variable  of  uniqueness,  the  average value  (mean)  overall  for  the  uniqueness  variable  is  4.11.  Favorable  variables,  the average  value  (mean)  overall  favorable  variables  is  4.25.  Overall  average  score (mean)  based  on  brand  image  variables  (strength,  uniqueness,  and  favorable)  Bio Organic  fertilizer  brand  "Pomi"  is  4.21.  The  average  value  (mean)  indicates  the positive brand image, because the average (mean) in more than 3, then the perceived brand image of farmers to fertilizer Bio Organics brand "Pomi" is positive.  And  The results showed brand awareness of farmers  in the position of brand recall as many as 69% were farmers place the bio-organic fertilizer brand "Pomi" in the second position in the pyramid of brand awareness.